22q11.2 deletion syndrome lowers seizure threshold in adult patients without epilepsy. (27th April 2017) - Wither, Robert G.; Borlot, Felippe; MacDonald, Alex; Butcher, Nancy J.; Chow, Eva W. C.; Bassett, Anne S.; Andrade, Danielle M.
Summary: Objective: Previous studies examining seizures in patients with 22q11.2 deletion syndrome (22q11.2DS) have focused primarily on children and adolescents. In this study we investigated the prevalence and characteristics of seizures and epilepsy in an adult 22q11.2DS population. Methods: The medical records of 202 adult patients with 22q11.2DS were retrospectively reviewed for documentation of seizures, electroencephalography (EEG) reports, and magnetic resonance imaging (MRI) findings. Epilepsy status was assigned in accordance with 2010 International League Against Epilepsy Classification. Results: Of 202 patients, 32 (15.8%) had a documented history of seizure. Of these 32, 23 (71.8%) had acute symptomatic seizures, usually associated with hypocalcemia and/or antipsychotic or antidepressant use. Nine patients (9/32, 28%; 9/202, 4%) met diagnostic criteria for epilepsy. Two patients had genetic generalized epilepsy; two patients had focal seizures of unknown etiology; two had epilepsy due to malformations of cortical development; in two the epilepsy was due to acquired structural changes; and in one patient the epilepsy could not be further classified. Significance: Similarly to children, the prevalence of epilepsy and acute symptomatic seizures in adults with 22q11.2DS is higher than in the general population. Hypocalcemia continues to be a risk factor for adults, but differently from kids, the main cause of seizures in adults with 22q11.2DS is exposure to antipsychotics and antidepressants. Further prospective studies are warranted to investigate how 22q11.2 microdeletion leads to an overall decreased seizure threshold.